2022
DOI: 10.3390/polym14061205
|View full text |Cite
|
Sign up to set email alerts
|

Study on Thermal-Oxidative Aging Properties of Ethylene-Propylene-Diene Monomer Composites Filled with Silica and Carbon Nanotubes

Abstract: In this work, a small amount of carbon nanotubes (CNTs) was used to partially replace the silica in ethylene-propylene-diene monomer (EPDM) to prepare EPDM composites via mechanical blending. The mechanical properties, thermal-oxidative aging properties and thermal stability of the composites were systematically investigated. The results showed that with the increase of CNTs content, the Shore A hardness and stress at 100% strain of the composites increased, while the elongation at break decreased. With the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…It can be seen from the figure that the addition of various fillers has different effects on the crosslinking density of composite materials, among which pure SIR has the lowest crosslinking density. The interactions between filler particles and rubber matrix also contribute to the crosslinking density [ 32 , 35 ], but no filler–rubber interactions in the pure SIR. After the addition of ATH, BN or Mica, the crosslinking density of the composite is nearly twice that of pure SIR, because after the addition of filler, a filler-matrix and filler–filler crosslinking network will be formed inside the composites.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen from the figure that the addition of various fillers has different effects on the crosslinking density of composite materials, among which pure SIR has the lowest crosslinking density. The interactions between filler particles and rubber matrix also contribute to the crosslinking density [ 32 , 35 ], but no filler–rubber interactions in the pure SIR. After the addition of ATH, BN or Mica, the crosslinking density of the composite is nearly twice that of pure SIR, because after the addition of filler, a filler-matrix and filler–filler crosslinking network will be formed inside the composites.…”
Section: Resultsmentioning
confidence: 99%
“…This decrease became more pronounced in elongation at break when the aging temperature surpassed 90 • C. Upon aging for 672 h, the elongation at break was reduced to 46.6% of its initial value. The tensile deformation of EPDM composites was affected by the increase in crosslinking density after aging, which inhibited the sliding of rubber molecular chains under external tension [29,38]. Consequently, the rubber molecular chains failed to fully absorb and dissipate external tensile energy during stretching, leading to a significant decrease in the elongation at break.…”
Section: Mechanical Properties Of Epdm Compositesmentioning
confidence: 99%
“…Related experimental studies have shown that the addition of CNTs can effectively improve the thermal-oxidative aging properties of rubber matrices. [35] Mean square displacement (MSD) is an important physical quantity that characterizes the ability of an additive to diffuse and migrate through a matrix. MSD refers to the average displacement of all particles from their respective initial positions at a motion time t. According to the Einstein equation, [36] the following correlation exists:…”
Section: Thermal-oxidative Aging Propertiesmentioning
confidence: 99%